Rate-Based Model In Bubble-Cup Batch Distillation Column - Nada B. Nakkash; Neran K. Ibrahim; Salah S. Ibrahim (Engineering and Technology Journal, 2009)
The present work concerned with studying the behavior of batchmulticomponent plate distillation tower using Rate-Base model (Non-Equilibrium model) theoretically and experimentally. The experimental work was performed by using a batch distillation column consisting of eight bubble-cup trays. A zeotropic (nonazeotropic) system of Benzene, Toluene, and Ethylbenzene (B-T-EB) has beenused. In the experimental work the effect of reflux ratio, heat duty, and initial charge composition on the batch distillation process have been studied. The range of reflux ratio was 1 - 4, heat duty was 222 and 336 Watt, and the initial charge composition was 0.2 - 0.5 mole fraction of the light component (benzene) and for the heavy component (ethylbenzene). The theoretical work was performed through several steps in order to construct and develop a model based on simultaneous heat and mass transfer between vapor and liquid phases called “Nonequilibrium or Rate-Based model”, which is based on MERSHQ equations (Material, Energy balances, Rate of mass and heat transfer, Summation of composition Hydrodynamic equation of pressure drop, and eQuilibrium relation The performance and validity of the developed non-equilibrium-based model gave a good agreement with the experimental work on Benzene-Toluene- EthylBenzene system.